An efficiency tool: application of CCR and SBM models in measuring commercial banks‘ performance in Malaysia / Norfarziah Adna ...[et al.] - Adna, Norfarziah; Mohamad, Siti Nurul Fitriah; Alias, Suriana; Mohd Yusof, Nazhatul Sahima; Hashim, Hazwani (Universiti Teknologi MARA Cawangan Kelantan, 2019)
Bank efficiency is very important in the banking industry. There are many methods involved to measure the efficiency of bank performance. This paper focuses on Slack Based Measure (SBM) and Charnes, Cooper, and Rhodes (CCR) model by comparing the result of efficiency. SBM gives the input excesses and output shortfalls for a decision many units (DMU) concerned. Meanwhile the CCR was interpreting as a reduction of the multiple outputs or multiple input situation for each DMU to a single “virtual output” and virtual input.” Furthermore, the result from this research states using SBM model give a value of input excesses and output shortfalls for each bank inefficient. The result also indicates that SBM score efficiency for bank inefficient is less than CCR score efficiency